2015
DOI: 10.1038/cddis.2015.185
|View full text |Cite
|
Sign up to set email alerts
|

2,4,5-Trimethoxyldalbergiquinol promotes osteoblastic differentiation and mineralization via the BMP and Wnt/β-catenin pathway

Abstract: Dalbergia odorifera has been traditionally used as a medicine to treat many diseases. However, the role of 2,4,5-trimethoxyldalbergiquinol (TMDQ) isolated and extracted from D. odorifera in osteoblast function and the underlying molecular mechanisms remain poorly understood. The aim of this study was to investigate the effects and possible underlying mechanisms of TMDQ on osteoblastic differentiation of primary cultures of mouse osteoblasts as an in vitro assay system. TMDQ stimulated osteoblastic differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 40 publications
6
60
0
Order By: Relevance
“…MAP kinases and NF-jB are essential for the induction of osteoblast differentiation-related genes via the activation of distinct cascades that target specific transcription factors, such as Runx2 [57,62]. In this study, rh-SHH-induced activation of Akt, p38, ERK, JNK, and NF-jB was attenuated by noggin, BMP-2 siRNA, and Cy.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…MAP kinases and NF-jB are essential for the induction of osteoblast differentiation-related genes via the activation of distinct cascades that target specific transcription factors, such as Runx2 [57,62]. In this study, rh-SHH-induced activation of Akt, p38, ERK, JNK, and NF-jB was attenuated by noggin, BMP-2 siRNA, and Cy.…”
Section: Discussionmentioning
confidence: 73%
“…The role of the BMP signaling pathway has been reported in osteoblastic/cementoblast differentiation [6,57]. Noggin directly binds to BMP-2, thereby preventing its interaction with BMP receptor [58].…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear localization, structural modification, and stabilization of β-catenin also served as an important part in osteoblast differentiation. 36 Furthermore, our study also showed that activated Wnt and BMP signaling pathways could upregulate the EMX2 expression, induce calcium salt deposition, increase mineralized nodules, and enhance ALP activity, thereby accelerating the process of MSCs differentiating into osteoblasts. 32 Increased expression of ALP, Col I, OPN, OPG/RANKL, and Runx2 played an important role in inducing osteoblast differentiation by activating the BMP and Wnt/β-catenin signaling pathways.…”
Section: Discussionmentioning
confidence: 54%
“…Mineralized nodule is typically observed as a late phase marker for terminal differentiation. MSCs can be stained for mineral deposition by Alizarin red [24]. Here we noted the negative impact of Osthole on the development of mineralized nodules by detecting the calcium influx with Fluo4-AM probe.…”
Section: The Influence Of Osthole Removal On Osteoblast Differentiationmentioning
confidence: 98%